ANALISIS HASIL PERCOBAAN ALAT PRAKTIKUM RUGI-RUGI ALIRAN DALAM PIPA - Yusuf, Nefli; Hariadi, Hariadi (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2021)
The phenomenon of flow in a pipe is one of the experiments carried out in the Mechanical Phenomenon Practicum in bachellor of Mechanical Engineering. In this paper, we will describe the experimental results of the tool that was made in mechanical engineering prgram, west sumatera muhammadiyah university for the first time. The pump used is large enough to 1.0 HP, it is expected that the pressure will be high enough and cause turbulent flow. Measuring instruments installed are Pressure Gauge, Stopwatch, and Water Meter. Water is pumped from the source (reservoir) in the form of a tub to a network of pipes with diameters of ¾